Faktor Penyebab Temuan Berulang pada Pemeriksaan Inspektorat - Mohamad Husni; Riyanthi Idayu; Nana Supriyatna (Politeknik Ganesha Medan, 2022)
The purpose of this study is to understand the factors that trigger the occurrence of repeated examination findings in the Inspectorate and evaluate the role of the Inspectorate's guidance to reduce the occurrence of repeated findings. The research uses qualitative methods with an exploratory approach. The results of the study show that: 1) Serang Inspectorate feels that there are still less competent audit personnel in developing related audit findings, because it is proven in the audit implementation stage that it still looks less precise/inappropriate; 2) Apparatus who have committed irregularities will behave unethically and also lose a sense of responsibility towards their work in the end the same deviation occurs again in the following year; 3) regulations that change but are not synchronized with proper and correct interpretations from the auditors and auditees can result in a high risk of error rate: 4) good and clean governance can be achieved if there is a commitment from the leadership with positive behavior which can ultimately minimize or can eliminate all audit findings that may be repeated; 5) sometimes communication with the auditee is not well established. Communication is only made after the audit is completed in the form of a request for the auditee's response through the concept of the audit result; 6) delegation of authority and responsibility, lack of knowledge of village heads and lack of good skills in preparing work plans and developing human resources in SKPD and Villages. Whereas all of that is one stage of the realization in the implementation of an internal control system; 7) knowledge is a high resource for an organization. Knowledge related to regional financial management is a basic thing that must be owned by the apparatus/employees in the finance department in each SKPD in order to be able to explain the function in terms of regional financial accountability as well as possible.